A feasibility and efficacy study of rapamycin and erlotinib for recurrent pediatric low‐grade glioma (LGG)1. Issue 1 (20th March 2012) - Yalon, Michal; Rood, Brian; MacDonald, Tobey J.; McCowage, Geoff; Kane, Rochelle; Constantini, Shlomi; Packer, Roger J.
Abstract Background To determine the toxicity and efficacy of rapamycin and erlotinib for the treatment of recurrent pediatric low‐grade gliomas (LGGs). Methods Patients <21 years of age with recurrent LGGs who had failed conventional treatment were eligible, including those with NF1. The treatment consisted of two phases, a feasibility portion which assessed the toxicity of erlotinib at 65 mg/m2/day once daily and rapamycin at 0.8 mg/m2/dose twice daily for 28 consecutive days. Results Nineteen (19) patients, median age of 8 years, with recurrent LGGs received the two‐drug regimen. Eight (8) of the patients had NF1. The combination of erlotinib and rapamycin was well tolerated and no patient was removed from study due to toxicity. All 19 patients were evaluable for response and one child, with NF1, had a partial response to treatment. Six (6) patients received the planned 12 courses of treatment. The reasons for stoppage of therapy before 1 year of treatment were poor compliance (1), parental desire for withdrawal (1), persistent vomiting which pre‐dated initiation of therapy (1), and radiographic progression (10). In those patients with stabilization of disease for 12 months or greater, 3 stayed on therapy and ultimately developed progressive disease, and one patient stopped therapy at 12 months and progressed. Two (2) patients, both with NF1, have had >1 year disease control. Conclusions The combination of rapamycin and erlotinib is well tolerated in children with LGGs. Objective responses were infrequent, although there was prolonged disease stabilization in some patients with LGGs, especially in two children with NF1. Pediatr Blood Cancer 2013; 60: 71–76. © 2012 Wiley Periodicals, Inc.